Monocarboxylate Transporter 4 (MCT4) Knockout Mice Have Attenuated 4NQO Induced Carcinogenesis; A Role for MCT4 in Driving Oral Squamous Cell Cancer - Bisetto, Sara; Whitaker-Menezes, Diana; Wilski, Nicole A.; Tuluc, Madalina; Curry, Joseph; Zhan, Tingting; Snyder, Christopher M.; Martinez-Outschoorn, Ubaldo E.; Philp, Nancy J. (Frontiers in Oncology, 2018)
Head and neck squamous cell carcinoma (HNSCC) is the 6th most common human cancer and affects approximately 50,000 new patients every year in the US. The major risk factors for HNSCC are tobacco and alcohol consumption as well as oncogenic HPV infections. Despite advances in therapy, the overall survival rate for all-comers is only 50%. Understanding the biology of HNSCC is crucial to identifying new biomarkers, implementing early diagnostic approaches and developing novel therapies. As in several other cancers, HNSCC expresses elevated levels of MCT4, a member of the SLC16 family of monocarboxylate transporters. MCT4 is a H+ - linked lactate transporter which functions to facilitate lactate efflux from highly glycolytic cells. High MCT4 levels in HNSCC have been associated with poor prognosis, but the role of MCT4 in the development and progression of this cancer is still poorly understood. In this study, we used 4- nitroquinoline-1-oxide (4NQO) to induce oral cancer in MCT4-/- and wild type littermates, recapitulating the disease progression in humans. Histological analysis of mouse tongues after 23 weeks of 4NQO treatment showed that MCT4-/- mice developed significantly fewer and less extended invasive lesions than wild type. In mice, as in human samples, MCT4 was not expressed in normal oral mucosa but was detected in the transformed epithelium. In the 4NQO treated mice we detected MCT4 in foci of the basal layer undergoing transformation, and progressively in areas of carcinoma in situ and invasive carcinomas. Moreover, we found MCT4 positive macrophages within the tumor and in the stroma surrounding the lesions in both human samples of HNSCC and in the 4NQO treated animals. The results of our studies showed that MCT4 could be used as an early diagnostic biomarker of HNSCC. Our finding with the MCT4-/- mice suggest MCT4 is a driver of progression to oral squamous cell cancer and MCT4 inhibitors could have clinical benefits for preventing invasive HNSCC.